Effect of heating on phosphate adsorption by soil - Chong, Jason Zhe Xin (2008)
The effect of soil heating at different temperatures (i.e 100 - 500°C) on phosphate adsorption have been investigated. The soil was obtained within the university campus. The final concentration of phosphate in solution was determined according to ascorbic acid method. The results of the batch experiments showed that percentage removal of phosphate decreased while the amount of phosphate adsorbed increased with increase in initial phosphate concentration. At a fixed initial phosphate concentration, the percentage removal of phosphate increased with increasing heating temperature from 100°C to 500°C. The value of maximum adsorption capacity also increased with increasing heating temperature. The adsorption data fitted to Langmuir or Freundlich isotherm depending on the heating temperature. Overall, heating the soil at high temperatures has a positive effect on phosphate adsorption.